To have and to hoax : a novel - Waters, Martha, 1988- (Atria Paperback, 2020)
"In this fresh and hilarious historical rom-com, an estranged husband and wife in Regency England feign accidents and illness in an attempt to gain attention--and maybe just win each other back in the process. Five years ago, Lady Violet Grey and Lord James Audley met, fell in love, and got married. Four years ago, they had a fight to end all fights, and have barely spoken since. Their once-passionate love match has been reduced to one of cold, detached politeness. But when Violet receives a letter that James has been thrown from his horse and rendered unconscious at their country estate, she races to be by his side--only to discover him alive and well at a tavern, and completely unaware of her concern. She's outraged. He's confused. And the distance between them has never been more apparent. Wanting to teach her estranged husband a lesson, Violet decides to feign an illness of her own. James quickly sees through it, but he decides to play along in an ever-escalating game of manipulation, featuring actors masquerading as doctors, threats of Swiss sanitariums, faux mistresses--and a lot of flirtation between a husband and wife who might not hate each other as much as they thought. Will the two be able to overcome four years of hurt or will they continue to deny the spark between them?"--